Design of Broadband Passive Optical Network Incorporating Different Modulation Formats and Colorless ONUs. Issue 1 (1st August 2022) - Sachdeva, Shippu; Gupta, Raghav
Abstract: In this work, a bidirectional broadband passive optical network (BPON) is proposed at 622.08 Mbps by incorporating colorless optical network units and different pulse shapes such as Duo-binary return to zero (DRZ), return to zero (RZ) and non-return to zero (NRZ). For varied link lengths, launching powers in terms of log BER, and Quality factor for downstream and upstream, the design of BPON is examined. The duo-binary advanced pulse shape outperformed the others in bidirectional BPON, achieving a symmetrical distance of 25 kilometres.